Multimorbidade de doenças cardiometabólicas e climatério: prevalência, padrões de doença e efeitos do exercício físico - Dechichi, Juliene Goncalves Costa (2022)
Introduction: Multimorbidity can be defined as the combination of two or more chronic diseases and affects more and more people around the world, especially in older women. The practice of physical exercise is an important tool to treat, prevent the progression and worsening of patients with multiple chronic diseases. Objective: To investigate whether 12-weeks of aerobic training changes cardiometabolic marker responses and climacteric symptoms in postmenopausal women with and without multimorbidities of cardiometabolic diseases. Methods: Forty one postmenopausal women were divided into two groups according to the number of cardiometabolic risk factors (hypertension, type 2 diabetes mellitus, dyslipidemia and obesity): MORB group (n = 18) with 1 risk factor; and MULTI group (n = 23) with ≥ 2 risk factors. Both groups were submitted in 12 weeks of aerobic training on track, 3x/week, lasting 40-50 minutes, with an intensity of 65%-75% HR reserve. Before and after training ambulatory blood pressure monitoring (ABPM), blood pressure variability (BPV), arterial stiffness, lipid and glucose profile, body composition and climacteric symptoms were measured. Climacteric symptoms were assessed using the Cervantes Quality of Life Scale (CS) and the Menopause Rating Scale (MRS). The Generalized Estimating Equation (GEE) with Bonferroni correction and intention-to-treat analysis was used to compare groups. Results: MULT group reduced (p<0.01) fat mass, waist circumference and body mass index, and increase (p<0.01) lean mass after training. No changes over time were found in blood lipids and glycemic indexes nor in ABPM, BPV and arterial stiffness in both groups. Both groups reduced (p<0.01) MRS scores after intervention with no difference between them. Conclusion: Aerobic training improved similarly body composition and climacteric symptoms, but did not change ABPM, BPV and arterial stiffness, nor blood lipids and glycemic indexes, in postmenopausal women with and without multimorbidities of cardiometabolic diseases.